Topos XIX-wiecznego Śląska w cyklu powieści historycznych Michaela Meinerta Hochwald-Saga (Saga Wysokiego Lasu) - Ratajczak, Marta (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article is devoted to the first three volumes of Michael Meinert’s Hochwald-Saga (The High Forest Saga) series, whose action takes place in Silesia in the 19th century; these are are: Gescheiterte Flucht (Failed Escape), Der zerrissene Graf (Lost count) and Ehrlicher Schwindler (Honest swindler). In these works, the author breaks away from the stereotypical perception of Silesia as a space of memory, the critical turning point of which was the end of World War II. He does not create images of a “lost homeland” – Silesia becomes an attractive historical space for him precisely because of its past character, and is a fascinating setting for novels with historical plots. At the same time, he revives the history of Silesia as a province of the Kingdom of Prussia and later of the German Empire. He also creates images of space, assigning them additional meanings, which is in line with the idea of space semantisation promoted by Yuri Lotman. An extremely important element in the composition of Meinert’s works is the creation of Silesia as a sacred space in which existential, axiological and theological questions are asked. In his understanding, places become a humanised space which has its own characteristic identity and often depicts the emotional states or character traits of the novel’s figures; moreover, it plays an important role in shaping their attitudes and values. The purpose of this text is to analyse the poetics of Meinert’s above-mentioned novels with particular emphasis on the topos of Silesia, its characteristics, and the role and functions it plays in them. As it is closely related to the poetics of place, attention is also paid to selected aspects of geopoetics in the sense proposed by Elżbieta Rybicka.